Menggagas Laporan Keuangan berbasis Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK EMKM) Bagi Pelaku Usaha Dodol Gorontalo - Melinda Ibrahim; Afriana Lomagio; Muhammad Ichsan Gaffar (Jurnal Pendidikan Akuntansi & Keuangan, 2023)
This study aims to assess the obstacles faced by Dodol Gorontalo MSME players in preparing financial reports based on SAK EMKM and designing a financial reporting system based on SAK EMKM. This research is a qualitative research with the Participation Action Research method. The stages of data analysis go through 4 (four) stages, namely: 1) Identifying the Research Question, 2) Gathering the information to answer the question, 3) Analyzing and interpreting the information, 4) Sharing the results with the participant. The results showed obstacles in accounting practices in Dodol Gorontalo MSMEs, namely accounting records are considered troublesome, complicated, and there is limited knowledge in financial management. Researchers designed a financial report format that is still manual in accordance with the SAK EMKM guidelines. This format is designed based on the specific needs and characteristics of the dodol business, namely cash receipts journal, cash disbursements journal, income statement and balance sheet.